Ḥannā Diyāb and his tales (Leiden)
xv, 399 sayfa
Keywords: “Ḥannā Diyāb and His Tales focuses on Ḥannā Diyāb, a Christian storyteller from Aleppo who originally narrated some of the world's most famous stories, among them “Aladdin“ and “Ali Baba.“ In the late spring of 1709, he told these tales in Paris to the scholar Antoine Galland, who published them in the concluding volumes of his French version of The Thousand and One Nights. Long entirely unknown, Diyāb's role went underacknowledged in scholarship on the Nights until recently. As a handbook, this volume brings some of the most important published scholarship on Diyāb together with new research, examining the sources of his tales and their reception, his interactions with Galland and Paul Lucas, and his literary environment in early eighteenth-century Aleppo.“ --